Przypadek Jednoczesnego Rozciągania i Skręcania Pręta o Przekroju Kołowym w Zakresie Sprężysto-Plastycznym - Michał Życzkowski (Engineering Transactions, 1955)
The problem is solved on the basis of Hencky's theory of plastic deformations. General equations are derived and boundary conditions stated. The general equations are integrated in an exact manner in the case of an incompressible material having Poisson's ratio equal to 1/2. In the case of a compressible material an approximate integration is carried out together with the evaluation of error.